Atheroprotective Vaccination with MHC-II Restricted Peptides from ApoB-100 - Tse, Kevin Y.; Gonen, Ayelet; Sidney, John; Ouyang, Hui; Witztum, Joseph L.; Sette, Alessandro; Tse, Harley Y.; Ley, Klaus (Frontiers in Immunology, 2013)
Background: Subsets of CD4+ T-cells have been proposed to serve differential roles in the development of atherosclerosis. Some T-cell types are atherogenic (T-helper type 1), while others are thought to be protective (regulatory T-cells). Lineage commitment toward one type of helper T-cell versus another is strongly influenced by the inflammatory context in which antigens are recognized. Immunization of atherosclerosis-prone mice with low density lipoprotein (LDL) or its oxidized derivative (ox-LDL) is known to be atheroprotective. However, the antigen specificity of the T-cells induced by vaccination and the mechanism of protection are not known. Methods: Identification of two peptide fragments (ApoB3501-3516 and ApoB978-993) from murine ApoB-100 was facilitated using I-Ab prediction models, and their binding to I-Ab determined. Utilizing a vaccination scheme based on complete and incomplete Freund’s adjuvant (1x CFA + 4x IFA), we immunized Apoe-/- mice with ApoB3501-3516 or ApoB978-993 emulsified in CFA once and subsequently boosted in IFA four times over 15 weeks. Spleens, lymph nodes and aortas were harvested and evaluated by flow cytometry and real time RT-PCR. Total atherosclerotic plaque burden was determined by aortic pinning and by aortic root histology. Results: Mice immunized with ApoB3501-3516 or ApoB978-993 demonstrated 40% reduction in overall plaque burden when compared to adjuvant only control mice. Aortic root frozen sections from ApoB3501-3516 immunized mice showed a >60% reduction in aortic sinus plaque development. Aortas from both ApoB3501-3516 and ApoB978-993 immunized mice contained significantly more mRNA for IL-10. Both antigen-specific IgG1 and IgG2c titers were elevated in ApoB3501-3516 or ApoB978-993 immunized mice, suggesting helper T-cell immune activity after immunization. Conclusion: Our data show that MHC Class II restricted ApoB-100 peptides can be atheroprotective, potentially through a mechanism involving elevated IL-10.